2016
DOI: 10.1021/acs.langmuir.6b00710
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Ultrathin Cross-Linked Metal Nanoparticle Films

Abstract: Here we report the preparation, characterization, and electrochemical study of conductive, ultrathin films of cross-linked metal nanoparticles (NPs). Nanoporous films ranging from 40 to 200 nm in thickness composed of gold and platinum NPs of ~5 nm were fabricated via a powerful layer-by-layer spin coating process. This process allows preparation of uniform NP films as large as 2 × 2 cm2 with precise control over thickness, structure, and electro-chemical and electrocatalytic properties. Gold, platinum, and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…16,17 Layer-by-layer deposition (LbL) of polyelectrolytes offers such a solution. 18 LbL deposition is a bottom up approach that has been leveraged to create a range of functional materials including reverse osmosis membranes, 19,20 polymer/clay re retardant coatings, 21,22 nanoparticle electrocatalysts 23,24 and Metal-Organic Frameworks (MOFs). 25,26,27 In its simplest form, a polyelectrolyte consists of an anionic polymer and a cationic polymer which are sequentially deposited on a substrate, forming one "bilayer" (BL).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Layer-by-layer deposition (LbL) of polyelectrolytes offers such a solution. 18 LbL deposition is a bottom up approach that has been leveraged to create a range of functional materials including reverse osmosis membranes, 19,20 polymer/clay re retardant coatings, 21,22 nanoparticle electrocatalysts 23,24 and Metal-Organic Frameworks (MOFs). 25,26,27 In its simplest form, a polyelectrolyte consists of an anionic polymer and a cationic polymer which are sequentially deposited on a substrate, forming one "bilayer" (BL).…”
Section: Introductionmentioning
confidence: 99%
“…Although high‐energy methods are able to construct large‐scale, high‐strength objects, they are not feasible for micro/nanoscale fabrication due to their precision limitation and the requirement for high‐energy source. Significant effort has been devoted to exploring methods for low‐temperature fabrication of metal nanostructures . Fluid‐interface‐assisted fabrication still remains as one of the few, if not the only, available methods to fabricate multi‐scale well‐designed structures out of metal particles .…”
mentioning
confidence: 99%
“…Optical/electrochemical experiments confirmed that with activation (+0.5 V for 5 s) of the metal film, detection of nanobubbles is more reproducible. This type of activation strategy has been widely used elsewhere . Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) were used to study the film morphology and surface composition across a larger area (hundreds of square microns).…”
Section: Resultsmentioning
confidence: 99%
“…This type of activation strategy has been widely used elsewhere. 35 Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) were used to study the film morphology and surface composition across a larger area (hundreds of square microns). SEM images with EDS mapping of the electrode surface before (Figure 2f) and after the electrochemical treatment (Figures 2g and S2c,d) indicate no obvious morphological or compositional changes occurred and the metal coating remains intact.…”
Section: ■ Results and Discussionmentioning
confidence: 99%